Projekty flagowe i kontekstowe w obszarach rewitalizacji - doświadczenia zagraniczne a polska praktyka = Flagship and contextual projects in revitalization areas - foreign experiences and the polish practice - Jadach-Sepioło, Aleksandra (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Large-scale projects of reconstruction andór revitalization of cities showcase their flagship projects, while in fact profound spatial changes in degraded areas arise primarily through numerous small contextual projects. Adaptations of existing, but frequently neglected or destroyed buildings for social, including educational or cultural, purposes are particularly important among such contextual projects. Occurring spatial changes are sometimes temporary and sometimes final. The first ones allow for the prototyping of solutions adapted to the needs of inhabitants; while the second ones either result from agreements with local communities or are imposed from above. The aim of the article is to present a typology of revitalization projects changing the space of a revitalized area from the perspective of these changes and of the target group.
Keywords: rewitalizacja; projekty flagowe; projekty kontekstowe; ewaluacja; gentryfikacja; revitalization; flagship projects; contextual projects; evaluation; gentrification